Factors Affecting Patient Safety in Working at the Madiun Hospital (RSUD Madiun) - Sumiati; Yuly Peristiowati; Indasah (Universitas STRADA Indonesia, 2023)
Patient safety in hospitals is a service system in a hospital that provides safer patient care. The purpose of the study was to analyze the factors that affect patient safety in working. The research design used was quantitative with cross-sectional approach. The population of all nurses in Madiun Hospital was 195 respondents. The sample of some nurses was 131 respondents with purposive sampling. The results showed that there was an influence on the role of communication (p=0.001), environmental conditions (p=0.003), distractions at work (p=0.014), workload (p=0.042) and staff education (p=0.000). Multivariate analysis showed that the most influential variable on patient safety was staff education with a significance level of p=0.000 and B=0.068. It is expected that nurses in providing health services must improve the quality which will be able to provide comfort and quality services to patients in terms of improving patient safety.